Consumer Response to Drug Risk Information: The Role of Positive Affect - Cox, Anthony D.; Cox, Dena; Mantel, Susan Powell (Journal of Marketing, 2010)
Risk disclosure is an essential element of the marketing of prescription drugs and other medical products. This study examines how consumers respond to verbal information about the frequency and severity of medical-product risks and how media-induced affect can moderate such responses. The study finds that consumers tend to overestimate the actual likelihood of adverse events described with words such as “common” or “rare” (compared with the probabilities such terms are typically intended to convey) and that consumers tend to give little weight to such probability language when forming product use intentions. However, consumers in positive media-induced moods seem to engage in more nuanced evaluation of product risk information, weighing both frequency and severity information and using such information to make inferences about other product attributes (e.g., product efficacy). These findings suggest that medical marketers and regulators need to devise more effective means of communicating risk probability to consumers and that positive mood induction (e.g., by placing advertisements in upbeat media environments) can enhance consumers’ ability to process product risk information.